Crustacea - Diarte-Plata, Genaro; Escamilla-Montes, Ruth (IntechOpen, 2020)
This book is divided into five sections. The first section is about Biology and Ecology, and includes the following chapters: "Crustacean", "The robber crab Birgus latro (Linnaeus, 1767)", "Scyllarid lobster biology and ecology", "Management of the interaction and cannibalism of postlarvae and adults of the freshwater shrimp Cryphiops caementarius (Molina, 1782)", "Bateman gradients and alternative mating strategies in a marine isopod", and "The habitat types of freshwater prawns (Palaemonidae: Macrobrachium) with abbreviated larval development in Mesoamerica (Mexico, Guatemala & Belize)". The second section, Fisheries, includes a chapter on the "Estimation of the maximum sustainable yield and the optimal fishing effort of the blue crab (Callinectes sapidus, Rathbun 1896) of Laguna Madre, Tamaulipas, Mexico". The third section, Genetics, covers "A comparison of genetic variation in two endemic thermal spring isopods, Thermosphaeroma thermophilum and T. milleri (Crustacea: Isopoda: Sphaeromatidae)". In the fourth section, Diseases, the chapter is "Phage therapy for control of bacterial diseases of crustaceans". The fifth section, Bioaccumulation, provides information on "Assessment of metal accumulation and bioaccumulation factor of some trace and heavy metals in freshwater prawn and crab". The book can be used by students, professors, and researchers in areas related to biological sciences.